Effects of Exergame Play on EF in Children and Adolescents at a Summer Camp for Low Income Youth - Flynn, Rachel M. (2014)
Past research has suggested exergame play improves adolescents’ executive function (EF) skills. EF change in 70 African American and Hispanic/Latino 10- to 16-year-olds participating in an inner-city summer camp was assessed following five 30-minute exergame play sessions. Children’s EF scores improved from pre- to posttest, and factors related to this change were examined. The number of exergame sessions the participants attended predicted posttest scores. In addition, level of achievement during game play was related to EF scores. Finally, the children’s level of enjoyment was not related to EF; however, frustration and boredom during game play were negatively related to EF. The findings are discussed in terms of their implications for the relationship between exergame play and cognitive benefits for adolescent players.